Role of Clotrimazole in Prevention of Recurrent Otomycosis. (26th December 2019) - Kiakojuri, Keyvan; Rajabnia, Ramazan; Mahdavi Omran, Saeid; Pournajaf, Abazar; Karami, Mohsen; Taghizadeh Armaki, Mojtaba
Abstract : Otomycosis is one of the relatively common diseases in the world which is caused by different fungi especially saprophytes. Concerning the relapse of this disease in a number of individuals, the present study was performed to evaluate the inhibitory effect of clotrimazole drop in the relapse of otomycosis. Clinical samples were taken by an ENT specialist from patients suspicious of having otomycosis. A part of these samples were stained, and others were cultured. The diagnosis of otomycosis was made on the basis of the recognizable and characteristic appearance of fungal hyphae or mycelium and fruiting bodies and/or conidiophores under microscopic examination. Patients with suspected otomycosis are not at risk of recurrence after treatment with clotrimazole drops. Out of the 161 individuals in whom definite diagnosis of otomycosis was made, the most affected individuals were, in the age range of 40–49 years, women, urban citizens, and housewives. Pruritus and diminished hearing were the main complaints of the patients. Aspergillus niger and A . flavus as well as Candida albicans were the main causes of the disease. The relapse of disease was observed in only five patients (3.1%), where A. niger was the main fungus. Most relapses were observed in women and in those with diminished hearing, manipulating the ears, ulcers in the canal, and tympanum. Our results suggested that usage of clotrimazole can be effective in reducing the relapse of otomycosis, and concerning the high cost of treating otomycosis while the low cost of using clotrimazole, usage of this drop is recommended to reduce the relapse of otomycosis.